Institutional partnerships in the rehabilitation of Biñan River, Laguna, Philippines - Escobin, Aileen A. (Journal of Environmental Science and Management, 2001)
This case study analyzed the institutional arrangements in the rehabilitation of Binan River in Laguna [Philippines]. Stakeholder involvement played a very significant role in the effort to rehabilitate the river. Through the initiatives of a grassroot organization, collective river rehabilitation activities that eventually involved other organizations were undertaken. Institionalization of multi-sectoral partnership through formal aggreements, availability of funds, and strengthened commitments of stakeholders were found to be crucial factors in enhancing participation in the river rehabilitation activities. The increased participation of various groups culminated in the formation of a multisectoral partnership that took the initiatives in taking care of the river. Community organizing through sectoral meetings, peer-to-peer communication, and environmental education campaigns were the effective steps for mobilizing the institutions. Strong leadership of the grassroots organization was found to be a critical factor in implementing river rehabilitation projects. After five years of activities, selected river water quality parameters indicated the progress of the rehabilitation efforts. Significant reductions in total suspended solids, oil/grease concentrations, BOD, and COD levels were observed.